2015
DOI: 10.4041/kjod.2015.45.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of the temporomandibular joint and mandibular dimensions after early correction of the maxillary arch form in patients with Class II division 1 or division 2 malocclusion

Abstract: ObjectiveThis study aimed to assess three-dimensional changes in the temporomandibular joint positions and mandibular dimensions after correction of dental factors restricting mandibular growth in patients with Class II division 1 or division 2 malocclusion in the pubertal growth period.MethodsThis prospective clinical study included 14 patients each with Class II division 1 (group I) and Class II division 2 (group II) malocclusions. The quad-helix was used for maxillary expansion, while utility arches were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…In a systematic review about sagittal changes after RME in Class II patients, 31 it was concluded that the studies found had methodological deficiencies with controversial or non-relevant sagittal effects. Coskuner and Ciger (2015) 18 verified that a Class II relationship can be corrected to a certain extent by slow expansion of the maxilla with a quadhelix; however, there was no significant effect on the TMJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review about sagittal changes after RME in Class II patients, 31 it was concluded that the studies found had methodological deficiencies with controversial or non-relevant sagittal effects. Coskuner and Ciger (2015) 18 verified that a Class II relationship can be corrected to a certain extent by slow expansion of the maxilla with a quadhelix; however, there was no significant effect on the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, one study was eliminated because it was a protocol proposal to be followed in future studies, 15 one for evaluating pre-and post-intervention changes through gypsum models and bite registration, 16 one for assessing condylar change by means of zonograms, 17 and five studies were excluded since they examined patients who underwent slow maxillary expansion. 10,[18][19][20][21] Therefore, seven articles from the systematic search were included for qualitative analysis; [22][23][24][25][26][27][28] as well as one record found by hand search (n ¼ 1); 29 totaling eight articles included in this review ( Table 1). A quantitative analysis was not feasible given the heterogeneity in the methodology of the selected articles.…”
Section: Selection and Characteristics Of The Studiesmentioning
confidence: 99%
“…La inclinación de la eminencia articular puede variar entre los individuos y determina la trayectoria de movimiento condíleo, así como el grado de rotación del disco sobre el cóndilo ( [1][2][3][4][5][6][7][8][9][10] ). La profundidad de la cavidad glenoidea varía y el desarrollo de la eminencia articular depende de los estímulos funcionales que tenga el cóndilo ( [11][12][13][14][15][16][17][18][19][20]. Estudios sugieren que la formación ósea de compensación de la cavidad glenoidea podría ayudar a soportar el aumento de las sobrecargas en la ATM que acompañan los cambios óseos degenerativos condilares ( 2,(11)(12)(13)(14)(15) ).…”
Section: Introductionunclassified
“…Una opinión que Rev Cient Odontol (Lima). 2019; 7 (1): [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Víctor Pardo Juárez se respalda por estos estudios es que el desarrollo de la eminencia articular y el cóndilo mandibular se ve más afectado por la función que por las características de la base del cráneo ( [15][16][17][18][19] ).…”
Section: Introductionunclassified
“…Various techniques are used to assess the condylar position in CBCT images of temporomandibular joints [6,7], emphasizing the sagittal and axial views as the main point. The condylar position obtained in sagittal and axial views are measured with little regard to the coronal view.…”
Section: Introductionmentioning
confidence: 99%